Response to adjunctive antibiotic therapy along with nonsurgical periodontal therapy in the treatment of peri-implantitis and chronic periodontitis patients: An exploratory review - Geetanshu Sethi; Vishakha Grover; Jyoti Gupta; Ashish Jain (Journal of Indian Society of Periodontology)
Objectives: This review was conducted to assess and compare whether there is a difference in response to adjunctive systemic and locally delivered antibiotics along with nonsurgical periodontal therapy (NSPT) in the treatment of peri-implantitis (PI) and chronic periodontitis (CP). Materials and Methods: A systematic search of literature on the predefined criteria was conducted using PubMed, Embase, and Scopus. Probing pocket depth, bleeding on probing, clinical attachment level, and microbial load reduction were selected as primary outcomes, whereas plaque index and gingival index were evaluated as secondary outcomes. Standard Cochrane risk-of-bias tools were used for the quality assessment of the included studies, and a qualitative data synthesis was conducted owing to the observed heterogeneity of the extracted data. Results: Adjunctive systemic and local antibiotics with NSPT resulted in additional beneficial effects in cases of both CP and PI, with greater improvement observed in cases of CP as compared to PI. Even for treatment of PI, among local antibiotics, minocycline was the only antibiotic with some significant adjunctive benefits, when used with NSPT as documented. Conclusion: Within the limitations of the review, it is concluded that the adjunctive use of antibiotics with NSPT offers a beneficial effect in the management of both CP and PI; however, there is insufficient direct evidence regarding the comparative efficacy of the adjunctive antibiotic therapy along with NSPT for the treatment of PI and CP.